The Political Role of the Army High Command during the Algerian Revolution (1960-1962) - seghiri, mounir (The Algerian Historical Journal, 2026)
Since its outbreak, the Algerian revolution depended on limited governing bodies, particularly the Front for National Liberation (FLN) and the Army for National Liberation (ALN). Nonetheless, the internal and external circumstances urged the leaders of the revolution to create other political and military bodies to be able to keep up with the various developments. These include the Interim Government of the Algerian Republic, The National Council for the Revolution, and the Army High Command. The latter was established by the beginning of 1960, and it made a military significance especial across Algeria’s eastern and western borders. As the negotiations approached, the Army High Command participated actively in the negotiation rounds, upholding an opinion of non-compromise to France and facing its political maneuvers to achieve as many strategic privileges as possible